Transmission of Severe Acute Respiratory Syndrome Coronavirus 2 via Close Contact and Respiratory Droplets Among Human Angiotensin-Converting Enzyme 2 Mice. (23rd May 2020) - Bao, Linlin; Gao, Hong; Deng, Wei; Lv, Qi; Yu, Haisheng; Liu, Mingya; Yu, Pin; Liu, Jiangning; Qu, Yajin; Gong, Shuran; Lin, Kaili; Qi, Feifei; et al.
Abstract: We simulated 3 transmission modes, including close-contact, respiratory droplets and aerosol routes, in the laboratory. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can be highly transmitted among naive human angiotensin-converting enzyme 2 (hACE2) mice via close contact because 7 of 13 naive hACE2 mice were SARS-CoV-2 antibody seropositive 14 days after being introduced into the same cage with 3 infected-hACE2 mice. For respiratory droplets, SARS-CoV-2 antibodies from 3 of 10 naive hACE2 mice showed seropositivity 14 days after introduction into the same cage with 3 infected-hACE2 mice, separated by grids. In addition, hACE2 mice cannot be experimentally infected via aerosol inoculation until continued up to 25 minutes with high viral concentrations. Abstract : Severe acute respiratory syndrome coronavirus 2 can be highly transmitted among naive angiotensin-converting enzyme 2 mice via close-contact spreading by respiratory droplets. However, these mice cannot be experimentally infected through aerosol inoculation unless it is continued for 25 minutes with a high viral concentration.